Green behavior: The intention and implementation of 3Rs behavior among UiTM Pahang students / Rozieana A Halid @ Khalid ... [et al.] - A Halid @ Khalid, Rozieana; Bahsri, Norizzati; Abd Aziz, Najihah; Mohamed Badri, Shamsul Nizam (2012)
This paper aims to study the willingness and behavior of UiTM Pahang Students in implementing reduce, reuse and recycle activities. Variables associated with the 3Rs behavior will be used to measure the extent of declared recycling, reuse and reduction behavioral intention and implementation. Data received from this study will be tabulated and analyzed using frequency, percentage and mean. At the end of the discussion, recommendations will be suggested in setting actions aim to encourage the recycle, reuse and reduce behaviors among UiTM Pahang Students.